Configuring thin client solution for Orang Asli community in Malaysia - Ahlan, Abdul Rahman; Mahmud, Murni; Arshad, Yusri (2010)
Orang Asli community is continuously given attention by the government for their development so as not to widen digital gap with other advanced races in Malaysia. IT education and access to computers and internets seem to be one of the noble viable options for the young generations to nurture the knowledge society values. This is due to many adverse reports related to Orang Asli attitudes and behaviours in the media as well as research publications. Thus, our IT social inclusion project is timely and hoped to contribute to their development for better lives. This paper describes the proposed thin client configuration for Orang Asli community in Gombak area. It begins with literature reviews on previous studies, concepts and products available and description of Orang Asli schoolchildren in the area. Based on risk management assessment, thin client system is chosen for the community and the proposed architecture configuration is described and illustrated.